A contemplation on the secondary origin of green algal and plant plastids - Eunsoo Kim; Shinichiro Maruyama (Acta Societatis Botanicorum Poloniae, 2014)
A single origin of plastids and the monophyly of three “primary” plastid-containing groups – the Chloroplastida (or Viridiplantae; green algae+land plants), Rhodophyta, and Glaucophyta – are widely accepted, mainstream hypotheses that form the basis for many comparative evolutionary studies. This “Archaeplastida” hypothesis, however, thus far has not been unambiguously confirmed by phylogenetic studies based on nucleocytoplasmic markers. In view of this as well as other lines of evidence, we suggest the testing of an alternate hypothesis that plastids of the Chloroplastida are of secondary origin. The new hypothesis is in agreement with, or perhaps better explains, existing data, including both the plastidal and nucleocytoplasmic characteristics of the Chloroplastida in comparison to those of other groups.